Os africanos e o mar: conhecimento e práticas à época da chegada dos portugueses (África, 1998)
Otextovisafazerumacontribuiçãoparaaconsolidaçãodeumahistóriamarítimaafricana,ouseja,umahistóriadocontatodaspopulaçõesafricanascom,emespecialnocasodacostaatlânticadocontinente,entreosriosdaGuinéeafozdoCuanza.Oobjetivoédestacaracontribuição(longamenteignoradapelahistoriografiaocidental)dospovosafricanosparaaconstruçãodochamado“mundoatlântico”.Paraissoaautorafazuminventáriodasavançadashabilidadesepráticasrelativasànavegação,construçãodeembarcações,atividadescomopesca,nado,guerras,navegaçãodecabotagemecomércio deváriospovosafricanos.Destacaaindaopapelimportantedasconchasecontascomomoedadetrocaemtodoocontinente.